Complete the expression adding the radicals.

10 sqrt(5) + 3sqrt(45) =13 sqrt ?

9 answers

To simplify the expression \(10\sqrt{5} + 3\sqrt{45}\) and express it in the form \(13\sqrt{x}\), we first simplify \(3\sqrt{45}\).

First, we can simplify \(\sqrt{45}\):

\[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} = 3\sqrt{5} \]

Now we can substitute this back into the expression:

\[ 3\sqrt{45} = 3(3\sqrt{5}) = 9\sqrt{5} \]

Now we can add this to \(10\sqrt{5}\):

\[ 10\sqrt{5} + 9\sqrt{5} = (10 + 9)\sqrt{5} = 19\sqrt{5} \]

To have it in the form \(13\sqrt{x}\), we can express \(19\sqrt{5}\) as follows:

\[ 19\sqrt{5} = 13\sqrt{x} \]

To find \(x\), we can set the coefficients equal to each other:

\[ 19\sqrt{5} = 13\sqrt{x} \]

If we divide both sides by 13, we get:

\[ \sqrt{x} = \frac{19}{13} \sqrt{5} \]

Squaring both sides gives us:

\[ x = \left(\frac{19}{13}\right)^2 \cdot 5 \]

Calculating \(\left(\frac{19}{13}\right)^2\):

\[ \left(\frac{19}{13}\right)^2 = \frac{361}{169} \]

Now substituting back:

\[ x = \frac{361}{169} \cdot 5 = \frac{1805}{169} \]

Thus, the completed expression is:

\[ 10 \sqrt{5} + 3 \sqrt{45} = 19\sqrt{5} = 13\sqrt{\frac{1805}{169}} \]

In conclusion, the answer is:

\[ x = \frac{1805}{169} \]

So \(10\sqrt{5} + 3\sqrt{45} = 13\sqrt{\frac{1805}{169}}\).

Complete the expression adding the radicals.

10 sqrt(5) + 3sqrt(45) = ?

To complete the expression \(10\sqrt{5} + 3\sqrt{45}\), we first need to simplify \(3\sqrt{45}\).

  1. Simplify \(\sqrt{45}\): \[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} = 3\sqrt{5} \]

  2. Substituting back: \[ 3\sqrt{45} = 3(3\sqrt{5}) = 9\sqrt{5} \]

  3. Now add the terms together: \[ 10\sqrt{5} + 9\sqrt{5} = (10 + 9)\sqrt{5} = 19\sqrt{5} \]

Therefore, the final expression is:

\[ 10\sqrt{5} + 3\sqrt{45} = 19\sqrt{5} \]

Complete the expression adding the radicals.

9 sqrt(5) + 3sqrt(45) = ?

To complete the expression \(9\sqrt{5} + 3\sqrt{45}\), we first simplify \(3\sqrt{45}\).

  1. Simplify \(\sqrt{45}\): \[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} = 3\sqrt{5} \]

  2. Substituting back into the expression: \[ 3\sqrt{45} = 3(3\sqrt{5}) = 9\sqrt{5} \]

  3. Now add the terms together: \[ 9\sqrt{5} + 9\sqrt{5} = (9 + 9)\sqrt{5} = 18\sqrt{5} \]

Therefore, the final expression is:

\[ 9\sqrt{5} + 3\sqrt{45} = 18\sqrt{5} \]

Complete the expression adding the radicals.

5 sqrt(5) + 3sqrt(45) = ?

To complete the expression \(5\sqrt{5} + 3\sqrt{45}\), we first simplify \(3\sqrt{45}\).

  1. Simplify \(\sqrt{45}\): \[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} = 3\sqrt{5} \]

  2. Substituting back into the expression: \[ 3\sqrt{45} = 3(3\sqrt{5}) = 9\sqrt{5} \]

  3. Now add the terms together: \[ 5\sqrt{5} + 9\sqrt{5} = (5 + 9)\sqrt{5} = 14\sqrt{5} \]

Therefore, the final expression is:

\[ 5\sqrt{5} + 3\sqrt{45} = 14\sqrt{5} \]

Complete the expression adding the radicals.

4 sqrt(5) + 3sqrt(45) = ?

To calculate the expression \( 4\sqrt{5} + 3\sqrt{45} \), we first need to simplify \( 3\sqrt{45} \).

  1. Simplify \(\sqrt{45}\): \[ \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \times \sqrt{5} = 3\sqrt{5} \]

  2. Substituting this back into the expression: \[ 3\sqrt{45} = 3(3\sqrt{5}) = 9\sqrt{5} \]

  3. Now add the terms together: \[ 4\sqrt{5} + 9\sqrt{5} = (4 + 9)\sqrt{5} = 13\sqrt{5} \]

Therefore, the final expression is: \[ 4\sqrt{5} + 3\sqrt{45} = 13\sqrt{5} \]

Similar Questions
  1. Square roots. Woohoo. Want to check some work I did.1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12]
    1. answers icon 2 answers
  2. Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work.sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2)
    1. answers icon 1 answer
  3. am I right?1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt
    1. answers icon 13 answers
    1. answers icon 1 answer
more similar questions